Perencanaan Dan Perancangan Rumah Susun Adaptif Banjir Pada Kawasan Kumuh Di Kota Denpasar: Bahasa Indonesia - Ganepa, Made Daynanda; Pradnyaningrum, Putu Siskha; Kurniawan, Agus; Nugraha, Putu Gede Wahyu Satya (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2026)
Flooding is a major problem in Denpasar City due to population growth, land conversion, and decreased environmental absorption capacity. This condition causes inundation in densely populated areas which impacts infrastructure damage, disruption of community activities, and decline in environmental quality and health. This study aims to design flood-adaptive housing in slum areas through a sustainable architectural approach that is not only responsive to the physical conditions of the environment, but also takes into account the social and economic aspects of the community. The method used is descriptive-analytical through literature studies, field observations, site analysis, and precedent studies to produce contextual and applicable design concepts. The design results show that adaptive strategies can be implemented through raising building elevations, using waterproof materials, providing flexible spaces, and rainwater management systems based on natural infiltration and drainage. In addition, the concept of communal and multifunctional spaces is also integrated to support social interaction and economic activities of the community. Vertical housing in the form of flats was chosen as a solution to land limitations while increasing space efficiency and the quality of the residential environment. Thus, this design is expected to be able to produce a housing model that is resilient, adaptive, inclusive, and sustainable against flood risks in urban areas.